The role of antihypertensive drugs in patients with preeclampsia and how to prevent it - I Gde Sastra Winata; I Wayan Agus Surya Pradnyana; Maria Septiana Parmonang Aroean (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. Preeclampsia, or hypertension in pregnancy, remains a serious problem that has negative short and long-term consequences for the mother and the baby.2. The use of antihypertensive medications has its own precautions as it they may harm the fetus.3. Prophylactic measures with minimal or moderate impact may be beneficial for mothers with hypertension in pregnancy.   ABSTRACT Treatment of hypertension in pregnancy, such as preeclampsia (PE), is still a difficult issue with negative short and long-term consequences for both the mother and the baby. Screening for preeclampsia at 11-13 weeks' gestation using a combination of maternal demographic characteristics and medical history with biomarker measurements can identify approximately 75% of women who develop premature preeclampsia with delivery at 37 weeks gestation and 90% of those with early preeclampsia. Preeclampsia has a 10% positive screen rate at 32 weeks. Another important worry on the use of antihypertensive medications during pregnancy is the potential harm to the fetus. Methyldopa, hydralazine, labetalol, and nifedipine are some common antihypertensive medications. Aspirin use is frequently related to a decrease in the prevention of early preeclampsia, but it must be accompanied by medication adherence. Aspirin can be coupled with heparin. Recent investigations on the use of furosemide and nifedipine in preeclampsia have also revealed a new combination.